Upper lip metastasis of sarcomatoid carcinoma of the lung – an unusual site of disease: a case report. (December 2017) - Le, Tri; Mayer, Melissa; Sailors, Joseph; Gerber, David; Truelson, John
Abstract Background Lip metastases are rare clinical events that are frequently mistaken for other diagnoses. For sarcomatoid lung carcinoma, a rare histologic variant of non-small cell lung cancer, the incidence and pattern of cutaneous spread is poorly understood. Case presentation We present a case of a 79-year-old African American man with a rapidly progressive upper lip cutaneous lesion that provided the first evidence of distant metastatic spread of sarcomatoid lung carcinoma. Conclusions This is the first reported case of lip metastasis in sarcomatoid lung carcinoma. It highlights the importance of maintaining a high level of suspicion for metastatic disease in the presence of new cutaneous findings as they may be the first evidence of advanced disease.